The importance of technological anxiety for the digital transformation of industrial processing companies in Poland - Młody, Michał; Weinert, Adam (Contemporary organisation and management. Challenges and trends, 2020)
The era of the fourth industrial revolution – which is gradually compelling companies to implement advanced machines and technologies and integrate such technology into the workplace, thereby creating a cyber-physical reality – brings a number of negative factors and phenomena that hinder transition. The aim of the article is to determine the significance of this technological anxiety for the digital transformation of manufacturing companies operating in the Polish industrial processing sector. The presentation of empirical results focuses on six dimensions of technological anxiety, i.e.: strategic planning, internal processes, change potential, standards and security, human resources and external barriers. The phases of their digital transformation, the level of employment, as well as the time they have been present in the market, were used as the prerequisites for differentiation across the research sample of 120 companies. The obtained results allowed for a partial verification of three research hypotheses and the indication of noticeable regularities in the examined area.